Exploration Behaviors, Body Representations, and Simulation Processes for the Development of Cognition in Artificial Agents - Schillaci, Guido; Hafner, Verena V.; Lara, Bruno (Frontiers in Robotics and AI, 2016)
Sensorimotor control and learning are fundamental prerequisites for cognitive development in humans and animals. Evidence from behavioural sciences and neuroscience suggests that motor and brain development are strongly intertwined with the experiential process of exploration, where internal body representations are formed and maintained over time. In order to guide our movements, our brain must hold an internal model of our body and constantly monitor its configuration state. How can sensorimotor control using such low-level body representations enable the development of more complex cognitive and motor capabilities? Although a clear answer has still not been found for this question, several studies suggest that processes of mental simulation of action-perception loops are likely to be executed in our brain and are dependent on internal body representations. Therefore, the capability to re-enact sensorimotor experience might represent a key mechanism behind the implementation of higher cognitive capabilities, such as behaviour recognition, arbitration and imitation, sense of agency and self-other distinction. Addressed mainly to researchers on autonomous motor and mental development in artificial agents, this work aims at gathering the latest development in the study on exploration behaviours, on internal body representations, on internal models, and on mechanisms for internal sensorimotor simulations. Relevant studies in human and animal sciences are discussed and a parallel to similar investigations in robotics is presented.